Bergenin, Acting as an Agonist of PPARγ, Ameliorates Experimental Colitis in Mice through Improving Expression of SIRT1, and Therefore Inhibiting NF-κB-Mediated Macrophage Activation - Wang, Kai; Li, Yun-fan; Lv, Qi; Li, Xi-ming; Dai, Yue; Wei, Zhi-feng (Frontiers in Pharmacology, 2018)
Bergenin, isolated from the herb of Saxifrage stolonifera Curt. (Hu-Er-Cao), has anti-inflammatory, antitussive and wound healing activities. The aim of the present study was to identify the effect of bergenin on experimental colitis, and explored the related mechanisms. Our results showed that oral administration of bergenin remarkably alleviated disease symptoms of mice with dextran sulfate sodium (DSS)-induced colitis, evidenced by reduced DAI scores, shortening of colon length, MPO activity and pathologic abnormalities in colons. Bergenin obviously inhibited the mRNA and protein expressions of IL-6 and TNF-α in colon tissues, but not that of mucosal barrier-associated proteins occludin, E-cadherin and MUC-2. In vitro, bergenin significantly inhibited the expressions of IL-6 and TNF-α as well as nuclear translocation and DNA binding activity of NF-κB-p65 in lipopolysaccharide (LPS)-stimulated peritoneal macrophages and RAW264.7 cells, which was almost reversed by addition of PPARγ antagonist GW9662 and siPPARγ. Subsequently, bergenin was identified as a PPARγ agonist. It could enter into macrophages, bind with PPARγ, promote nuclear translocation and transcriptional activity of PPARγ, and increase mRNA expressions of CD36, LPL and ap2. In addition, bergenin significantly up-regulated expression of SIRT1, inhibited acetylation of NF-κB-p65 and increased association NF-κB-p65 and IκBα. Finally, the correlation between activation of PPARγ and attenuation of colitis, inhibition of IL-6 and TNF-α expressions, NF-κB-p65 acetylation and nuclear translocation, and up-regulation of SIRT1 expression by bergenin was validated in mice with DSS-induced colitis and/or LPS-stimulated macrophages. In summary, bergenin could ameliorate colitis in mice through inhibiting the activation of macrophages via regulating PPARγ/SIRT1/NF-κB-p65 pathway. The findings can provide evidence for the further development of bergenin as an anti-UC drug, and offer a paradigm for the recognization of anti-UC mechanisms of compound with similar structure occurring in traditional Chinese medicines.